The experience of Jewish liturgy : studies dedicated to Menahem Schmelzer - Blank, Debra Reed. (The Brill Reference Library of Judaism, 2011)
Menahem Schmelzer, widely recognized for his expertise in Jewish manuscripts and piyyut, has also influenced Jewish liturgical research of the past half century. This collection of sixteen academic studies, by Israeli, European, and American scholars, honors Schmelzer's contribution. The contributors represent three generations, and their topics and methods testify to the vast subject area that Jewish liturgy has become. The articles explore a wide variety of texts and ritual occasions, the relationship between text and worship experience, and implications for related areas such as mysticism; most apply the methods of other subject areas such as liguistics to liturgical study and its implications for related fields. \'...this volume, as a whole, is as much a testimony to the enduring centrality of the librarian in scholarship as it is a collection of essays on \'the experience of Jewish liturgy.\' Wide ranging in scope, these essays are an accurate snapshot of the state of research, illustrating the wealth of material awaiting publication, the need for revisiting prior assumptions, and also the limits of our scholarship.\' Yoel Kahn, Congregation Beth El, Berkeley